AB0391 Cardiovascular risk assessment in rheumatoid arthritis patients using the score chart. (23rd January 2014) - Rosales Alexander, J.L.; Magro Checa, C.; Salvatierra, J.; Cantero Hinojosa, J.; Raya Alvarez, E.
Abstract : Background: The European League Against Rheumatism (EULAR) published evidence-based recommendations to guide in the cardiovascular (CV) risk management in rheumatoid arthritis (RA) patients and other forms of inflammatory arthritis. In RA patients, CV risk is calculated according to the SCORE by the application of a multiplier factor 1, 5 in those who meet some clinical criteria. EULAR recommends to use local guidelines for CV risk management. In our country the SCORE chart has been calibrated for Spain, although it is not systematically applied to our patients. Objectives: To assess CV risk in RA patients using the South European SCORE chart (Eu-SCORE) and compare it with the SCORE chart calibrated for Spain (S-SCORE) following the EULAR recommendations. To analyze the factors that predict a higher CV global risk using the S-SCORE chart. Methods: We included 201 consecutive patients diagnosed of RA according to the 1987 classification criteria of American College of Rheumatology (ACR) followed in our outpatient clinics. We recorded demographic data, classic CV risk factors, previous ischemic events, clinical and laboratory parameters of disease activity, lipid profile and RA characteristics. We calculated CV risk using both SCORE charts following the EULAR recommendations. Data were collected in Excel 2007 and analyzed with the statistical software SPSS 15. Descriptive data were shown as percentages and mean ± standard deviation (SD). Differences between qualitative variables were assessed using Chi-squared test or McNemar's test and for comparing means we used the ANOVA Bonferroni adjustment. The limit of statistical significance was located in the α error of 0, 05. Results: Most patients were women 160 (79, 6%), 75 (37%) patients had more than 10 years of disease evolution and 78 (39%) patients met the clinical criteria for the EULAR recommendations. Using the Eu-SCORE the mean ± SD score was 2, 6±2, 9 and with the S-SCORE was 3, 3±4. A change in the CV risk occurred after applying both SCORE charts in 27 (55, 8%) patients. Eight (9, 8%) patients with low risk were reclassified into intermediate risk. Likewise, 19 (29, 7%) patients with intermediate risk were reclassified into high risk after applying the S-SCORE (p<0, 001). Of the analyzed variables, the levels of CRP (p<0, 034), extra articular manifestations (p<0, 048) and disease lasting more than 10 years (p<0, 001) seem to predict a higher global CV risk using the S-SCORE. Conclusions: The use of the S-SCORE chart involves an overestimation of the CV risk in comparison with the application of the Eu-SCORE, what could have implications in management of these patients. The factors that predict a higher global CV risk using the S-SCORE seem to be the levels of CRP, extra articular manifestations and disease lasting more than 10 years. References: MJL Peters et al. EULAR evidence-based recommendations for cardiovascular risk management in patients with rheumatoid arthritis and other forms of inflammatory arthritis. Ann Rheum Dis 2010; 69: 325-31. Gόmez-VaqueroC et al. Assessment of cardiovascular risk in rheumatoid arthritis: Impact of the new EULAR recommendations on the score cardiovascular risk index. Clin Rheumatol. 2012 Jan; 31(1):35-9. Disclosure of Interest: None Declared